Kantian anthropology: a science like no other - LOUDEN, Robert B. (Faculdade de Filosofia e Ciências, 2021)
In this essay I begin by examining Kant’s criteria for “proper science” as presented in the Preface to his Metaphysical Foundations of Science, and then ask whether Kantian anthropology can possibly qualify as a proper science according to these demanding criteria. I defend a qualified ‘yes’ answer to this question, while also drawing attention to several less tidy aspects of his anthropology project that are difficult to fit onto the Procrustean bed of science.